A Survey on the Principle of Church Finances and its Impact on Church Growth in the New Covenant Church, Ibadan, Nigeria - Falaye, T. A. (NIU Journal of Humanities, 2021)
Every church should have and operate on an adequate budget. Not only is it a useful management tool, but it can help pastors teach stewardship to their congregation. This paper examined the implication of effective church budgeting on the growth of the New Covenant Church. This paper established that some of the churches that use the budget as a tool that controls and guide the church resources and finances experienced growth numerically, financially, and spiritually. This study further established that the contributions of effective church budgeting in the New Covenant Church could be further enhanced if each leadership and members consider its outcome. This paper revealed the brief history, mission statement, doctrinal principles, and the source of income in the New Covenant Church. Different literature books relevant to the study were consulted together with internet sources as well as an interview of the pastor and member of the New Covenant Church. This study highly recommends that financial management in every church should be effectively handled by those that have an understanding of finances to accommodate growth, and this, however, can be actualized if the whole church sees the need for it, especially each department in the church. Keywords: Finances, Church, Growth, Budgeting